Persistent cognitive deficits in ACL-injured athletes despite of rehabilitation: an observational longitudinal study - Jesús Jiménez-Martínez; Jesús Jiménez-Martínez; Francisco Alarcón-López; Luis Javier Chirosa-Ríos; Luis Javier Chirosa-Ríos; Alejandro Gutiérrez-Capote; Alejandro Gutiérrez-Capote; David Cárdenas-Vélez; David Cárdenas-Vélez (Frontiers in Sports and Active Living)
BackgroundRehabilitation programs following an anterior cruciate ligament (ACL) injury tend to focus on improving conditional aspects such as biomechanics. Recently, some studies have analyzed the relationship between cognition and ACL injury, but how cognitive performance evolves throughout the rehabilitation process has not yet been explored. This study assessed how cognitive performance evolves at three points in the ACL injury recovery process: preoperatively, postoperatively, and at the end of the rehabilitation process. It also aims to compare cognitive performance at the end of the rehabilitation process with athletes without a history of ACL injury.Methods30 open-skill sports athletes who had recently sustained an ACL injury and 30 open-skill sports athletes with no history of ACL injury were recruited. For the group of ACL-injured athletes, three experimental sessions were conducted at three different points in the ACL injury recovery process. For the control group a single experimental session was conducted. During the experimental sessions participants performed Flanker Task and Multiple Object Tracking to evaluate their cognitive performance.ResultsFor both Flanker and MOT task, ACL injury athletes show better cognitive performance postoperatively compared to the preoperative phase. For example, a higher mean reaction time in the Flanker task (BF₁₀ = 4.14) and lower accuracy in 3-ball tracking at 28.8 deg/s (BF₁₀ = 2.45). Nevertheless, no improvement was observed between the postoperative and follow-up phases. Finally, ACL injury athletes did not reach a cognitive performance comparable to healthy athletes, for example on mean reaction time in the Flanker Task (BF₁₀ = 60.64) and the 3-ball tracking at speeds of 19.9 and 28.8 deg/s (BF₁₀ = 16.30, BF₁₀ = 12.12, respectively).ConclusionsACL injury athletes show improvements in cognitive performance post-surgery, but it stabilizes at the end of the rehabilitation and remains lower than that of athletes who did not suffer an ACL injury. Therefore, ACL rehabilitation programs fail to improve cognitive performance, increasing the risk of suffering a new ACL injury compared to those without a history of ACL injury.